Present and Active: Unpacking The Negotiated Logics of Container Street Traders in the Governance of a Ghanaian city - Amoah, Samuel Twumasi (Department of Environmental and Geographical Science, 2023)
This research addresses a gap in contemporary scholarship on street trading and its governance in Ghanaian cities which predominantly focuses on the exclusionary policies that limit and, in some instances, aim to eliminate street trading. Container street traders play critical roles in the everyday governance of city streetscapes in Wa, a city in the Upper West Region of Ghana. In negotiating access to space by either renting, perching, buying, or constructing container stalls and setting up their trade, they shape the street and its built environment. Providing access to goods and services, container traders contribute to the street economy. Traders encounter and engage with a range of city actors in their everyday trading lives. They negotiate access to space, comply with regulations that govern the building of trading space and trade itself. In this thesis I examine the roles traders play in city governance, the logics which shapes the ways traders are legitimate actors, present and active in the city's streetscape. By examining street traders' negotiated logics (NL), the vital and diverse roles they play in city governance, I reposition the dominant conceptualisations of street traders, by portraying the varied ways container traders shape the city's streetscape and the regulations governing their trade. I draw on in-depth interviews and participant observations with traders and various city actors including land and container owners, city officials, and their representatives, I analyze the varied micro-practices that sustain trade, shape traders varied negotiated logics, and their roles in the city governance. Some traders enter street trading to make do, to survive. Others do so to move up, build a business, and become entrepreneurs. Some traders in their quests to reorganise their lives use street trading as a way of building an anchor and refuge in the city. These varied negotiated logics shape the ways in which traders engage with city officials and regulations, specifically how they navigate paying tolls, fees, and rents. Some traders participate and comply with regulations to maintain the rights to trade and not to worry. Some traders work to renegotiate to postpone and delay compliance, while some dodge regulations by being strategically absent. In making this argument, I contribute to calls in current scholarship to acknowledge the heterogeneity of street trade and its varied roles in city governance. Rather than victims, street traders are critical actors whose varied and negotiated trading logics shape city governance, its built environment, and the street economy.